2023
DOI: 10.3390/ijms25010394
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Stem Cell-Based Therapies in the Treatment of Osteoarthritis

Ye Chen,
Rui-Juan Cheng,
Yinlan Wu
et al.

Abstract: Osteoarthritis (OA) is a chronic, degenerative joint disease presenting a significant global health threat. While current therapeutic approaches primarily target symptom relief, their efficacy in repairing joint damage remains limited. Recent research has highlighted mesenchymal stem cells (MSCs) as potential contributors to cartilage repair, anti-inflammatory modulation, and immune regulation in OA patients. Notably, MSCs from different sources and their derivatives exhibit variations in their effectiveness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 128 publications
0
0
0
Order By: Relevance
“…Its GO terms focus on functions such as protein synthesis and transportation, adding that representative genes of catabolism such as MMP3 are specifically expressed in this subtype, indicating that this subtype is a group of chondrocytes with active synthesis and catabolism process. The balance between synthesis and catabolism in chondrocytes is the driving force for cartilage tissue to maintain and renew its ECM ( 19 , 20 ). Moreover, previous research has demonstrated the potential of METRNL in mitigating inflammation and pyroptosis in osteoarthritis ( 21 ), combined with METRNL+ subtype mainly comes from healthy cartilage, which suggest the cartilage protective effect of this subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Its GO terms focus on functions such as protein synthesis and transportation, adding that representative genes of catabolism such as MMP3 are specifically expressed in this subtype, indicating that this subtype is a group of chondrocytes with active synthesis and catabolism process. The balance between synthesis and catabolism in chondrocytes is the driving force for cartilage tissue to maintain and renew its ECM ( 19 , 20 ). Moreover, previous research has demonstrated the potential of METRNL in mitigating inflammation and pyroptosis in osteoarthritis ( 21 ), combined with METRNL+ subtype mainly comes from healthy cartilage, which suggest the cartilage protective effect of this subtype.…”
Section: Discussionmentioning
confidence: 99%